2020
DOI: 10.1167/iovs.61.5.46
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Fat Volume After Treatment with Topical Prostaglandin Agonists

Abstract: Topical prostaglandin analogs (PGAs) are common treatment for primary openangle glaucoma (POAG) but reportedly may cause adnexal fat atrophy. We asked if patients with POAG treated with PGAs have abnormalities in orbital fat volume (OFV). METHODS. We studied 23 subjects with POAG who had never experienced intraocular pressure (IOP) exceeding 21 mm Hg and were treated long term with PGAs, in comparison with 21 age-matched controls. Orbital volume, non-fat orbital tissue volume, and OFV were measured using high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…We did not exclude subjects who had been treated for IOP reduction with topical prostaglandin agonists, since nearly all patients with POAG are treated as first-line therapy with these drugs. We have shown that topical prostaglandin agonists do not alter anterior orbital fat in the regions exposed to these drugs 20 and multivariate analysis has not demonstrated a statistical effect of exposure to these drugs on globe retraction during adduction tethering. 5 We only selected for analysis all subjects who underwent target-controlled MRI in central gaze and smaller and larger angles of adduction who demonstrated minimal ON redundancy (path length <102.5% over minimum straight-line path) in both adduction positions.…”
Section: Methodsmentioning
confidence: 71%
“…We did not exclude subjects who had been treated for IOP reduction with topical prostaglandin agonists, since nearly all patients with POAG are treated as first-line therapy with these drugs. We have shown that topical prostaglandin agonists do not alter anterior orbital fat in the regions exposed to these drugs 20 and multivariate analysis has not demonstrated a statistical effect of exposure to these drugs on globe retraction during adduction tethering. 5 We only selected for analysis all subjects who underwent target-controlled MRI in central gaze and smaller and larger angles of adduction who demonstrated minimal ON redundancy (path length <102.5% over minimum straight-line path) in both adduction positions.…”
Section: Methodsmentioning
confidence: 71%